Millimeter waves as a source of selective heating of skin. Issue 6 (16th July 2015) - Zhadobov, Maxim; Alekseev, Stanislav I.; Le Dréan, Yves; Sauleau, Ronan; Fesenko, Evgeny E.
<x xml:space="preserve">Abstract</x> This study demonstrates that 20–100 GHz range can be used for spatially‐accurate focusing of heating inside the skin achieved by varying frequency and exposure beam size, as well as by enforcing air convection. The latter is also used to reduce overheating of skin surface. Heating at different skin depths depending on these parameters is investigated in detail using the hybrid bio‐heat equation. In particular, it is shown that decreasing frequency and/or increasing exposure beam size at forced airflow result in elevation of heating of deeper layers of tissue and decrease of skin surface temperature. Changes of water content within 15%, which exceed those due to aging and presence of tumors, only slightly affect heating. Exposure intensity necessary to reach a target temperature significantly increases in different areas of body with elevated blood flow. Dependence on exposure intensity and hyperthermia treatment duration is also investigated and discussed. Results of this study suggest that the lower part of the millimeter‐wave range is an attractive alternative for non‐invasive thermal treatment of skin cancer with a high spatial resolution. Bioelectromagnetics. 36:464–475, 2015. © 2015 Wiley Periodicals, Inc.